The usage of short story via phone application: enhancement and motivation among second language learners - Abd Rahim, Normaliza; Adzharuddin, Nor Azura (Sakarya University, 2018)
The study focuses on the use of short story via phone application among second language learners. The samples of the study consist of 21 subjects from two classes of Malay language. The subjects were given a story entitled “The Fox” from the phone application. The subjects were to watch the story for three weeks. Then, the subjects rewrite the story and the essays were marked accordingly. The results of the story revealed that majority of the subjects managed to write the character, characteristic and storyline of the story. The study also revealed that the subjects managed to write the correct vocabulary, sentence structure and spelling in their writings. In addition to that, short story via phone application enhances the subjects learning in the second language and motivates subjects learning in the classroom. It is suggested that future studies will focus on other short stories using the phone application.